Membangun Fondasi Keuangan Berkelanjutan Bagi Sociopreneur - Oktaviani, Astri Oktaviani; Handika Pradipta; Muhammad Rifai (Universitas Pamulang, 2025)
This Student Community Service (PMkM) aims to build a sustainable financial foundation for sociopreneurs, especially among students of SMK IPTEK South Tangerang, considering the significant challenges in accessing capital in Indonesia. The method employed was interactive offline socialization, involving 23 Accounting students from Pamulang University and 39 Accounting students from SMK IPTEK South Tangerang. The socialization material covered basic concepts of sociopreneurship, various alternative funding sources, and adaptive financial management strategies that integrate financial goals and social impact. The contribution of this research lies in increasing participants' financial literacy and awareness regarding the importance of financially independent business models to support social missions. The results indicate a new understanding and behavioral changes in viewing entrepreneurship as a means of sustainable social transformation. Keywords: Sociopreneurship; Sustainable Finance; Social Impact